Odhod v prvo samostojno stanovanje - Mandič, Srna (Družboslovne razprave, 2007)
The article deals with people's first autonomous housing after they leave home; by building on the literature and using data from the European Survey of Quality of Life it focuses on two issues. First, it compares the time people leave home among EU member states and confirms similarities among the new member states and the southern European states which are both witness to the late leaving of home; however, significant differences are also found among the new member states and their subgroups that call for further consideration. Second, the availability of housing as a structural factor is tested for its impact on the time of leaving home among countries and a statistically significant correlation is found between the size of the rental housing stock and the time of leaving home.
Keywords: Kakovost življenja; Quality of life; standard of living; Stanovanjsko vprašanje; Housing question; Young adults; Mladi odrasli; Države Evropske unije; European Union countries; mladi; samostojnost; primerjalna analiza; Evropska unija; European Union